The recent past of physical education in the Portuguese-Brazilian context: a new self-understanding (Research, Society and Development, 2021)
This essay aims to present the points that determined the reconceptualization of Physical Education in the Portuguese-Brazilian context. From the Portuguese perspective, the 1960’s marked the transformation process of the traditional Physical Education. In this context, it is observed that the need for change was enhanced by the scientific discourse and, unquestionably, by the rise of Sport at the time. In the Brazilian context, it is noted that the 1980’s is the milestone in the Sport schooling process. Namely, it is at this stage of history that the sports discourse loses space for critical pedagogical conceptions that possibly seek to bring Physical Education closer to the sociocultural bias. Therefore, it is found that there is a short “civilization curve” that distinguishes the discourse and paradigmatic lines of the highlighted countries. There is, in addition, strong evidence that indicates that sociopolitical issues, and a whole set of extracurricular practices, directly or indirectly, influence the Physical Education dimension, especially in the Brazilian context. Nevertheless, it is perceived that, regardless of the paradigmatic line assumed, of the context, precisely, founding and dignifying the profession has always been (still is) the greatest challenge! The complexity is in preserving the legitimacy, the authenticity of the area itself. A desire that requires struggles and interventions on various dimensions. Only a new self-understanding is not enough.